2017
DOI: 10.1051/sicotj/2016052
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation of proximal femoral nail in unstable trochanteric fractures

Abstract: -Introduction: Biomechanically proximal femoral nail (PFN) is a better choice of implant, still it is associated with screw breakage, cut out of screw through femoral head, Z effect, reverse Z effect, and lateral migration of screws. The purpose of this study is to evaluate the results of augmented PFN in terms of prevention of postoperative complications and failure rates in unstable trochanteric fractures. Material and methods: We carried out a prospective study of 82 cases with unstable trochanteric femoral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 22 publications
2
27
0
Order By: Relevance
“…In our series complications are less as comparable to the technical and mechanical complications described in literature [8] [14] [22] [24] [25]. Our findings indicate that the use LATERAL PLATE beneficial in restoring anatomy of proximal femur which prevents loosening of screws and helps in union.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…In our series complications are less as comparable to the technical and mechanical complications described in literature [8] [14] [22] [24] [25]. Our findings indicate that the use LATERAL PLATE beneficial in restoring anatomy of proximal femur which prevents loosening of screws and helps in union.…”
Section: Resultssupporting
confidence: 84%
“…Author believes that improved bony contact between proximal and distal fragments by stabilization of the comminuted lateral wall is likely to improve the chances of union and maintenance of adequate lever arm [8]. However this method is not useful when the trochanter is fragmented.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gadegone et al in their study comprising 82 fractures average time for union was 14.2 weeks. 8 Yadkikar et al in their study of 39 cases Average fracture union time was 16 weeks. The mean pre-injury MHHS was 74 (Maximum of which was 91).…”
Section: Discussionmentioning
confidence: 96%
“…In a study by Pajarinan et al [8] , they found that fixing the unstable intertrochanteric fractures initially in a slightly valgus position helps in preventing the excessive varus that may occur during initial 6 weeks. In the article published in 2017 SICOT, Wasudeo M. Gadegone et al [9] went one step ahead to find the solution to prevent the implant failure in unstable intertrochanteric fractures by augmenting the fixation by additional Poller screw missing the nail or by using encerclage wire thereby preventing the lateral blow out. But in the critical analysis from the Norwegian Hip fracture register between 2005 to 2010, based on the observation of 7643 operated Type A1simple two part fractures Kjell Matre MD [10] et al concluded that sliding hip screw is better in Type A1 simple two part fractures than intramedullary nails like PFN as the latter is associated with more number of reoperations within 1st postoperative year Good anatomical reduction of the fracture, and proper positioning and length of the lag screw and derotation screws are crucial for the PFN procedure and reported to yield excellent outcomes [11,12] .…”
Section: Discussionmentioning
confidence: 99%